The effect of prior treatment on clinical outcomes in patients with achalasia undergoing peroral endoscopic myotomy - Liu, Zu-Qiang; Li, Quan-Lin; Chen, Wei-Feng; Zhang, Xiao-Cen; Wu, Qiu-Ning; Cai, Ming-Yan; Qin, Wen-Zheng; Hu, Jian-Wei; Zhang, Yi-Qun; Xu, Mei-Dong; Yao, Li-Qing; Zhou, Ping-Hong (Endoscopy, 2019)
Background Peroral endoscopic myotomy (POEM) is a treatment option for patients with previous surgical or endoscopic treatment. We aimed to evaluate the influence of prior treatment on perioperative and follow-up outcomes in patients undergoing POEM.Methods From August 2010 to December 2014, a total of 1384 patients with achalasia underwent POEM at our center. We retrospectively reviewed 849 patients who completed follow-up. Patients with an Eckardt score ≥ 4 after POEM were considered to have a clinical failure. We compared variables between patients with and without prior treatment. We analyzed risk factors for perioperative major adverse events, and clinical reﬂux and failure during follow-up. Results 245 patients (28.9 %) had undergone prior treatment, and 34 patients (4.0 %) experienced a major adverse event associated with the POEM procedure. During a median follow-up of 23 months (range 1 – 71), clinical reflux occurred in 203 patients (23.9 %) and clinical failure was recorded for 94 patients (11.1 %). Patients with prior treatment had a longer procedure duration (P = 0.001) and longer hospital stay after POEM (P = 0.001). Prior treatment was not an independent risk factor for major adverse events or clinical reflux (odds ratio [OR] 1.19, P = 0.65; OR 1.26, P = 0.19; logistic regression), but it did increase the rate of clinical failure during follow-up (hazard ratio 1.90, P = 0.002; Cox regression). Conclusions POEM was performed safely with a low rate of major adverse events in patients with achalasia who had undergone prior surgical or endoscopic treatment. However, prior treatment increased the risk of clinical failure after POEM.